PENGELOLAAN WAKAF UANG TUNAI PADA LEMBAGA DARUT TAUHID (DT) PEDULI KOTA SUKABUMI - WAHYUNI ABDUN; TOTOH ABDUROHMAN (DIRHAM Jurnal Ekonomi Islam, 2020)
This study is intended for getting information about the strategy of developing cash waqf at the institution of Daarut Tauhiid Peduli, Sukabumi. Another purpose was also to find out the law of cash waqf in the view of muamalah fiqih and the law based on the fatwa of Indonesian Ulama Council (MUI). The techniques of data collection for this study were interviews conducted direct communication, and also by phone. The method of analysis was descriptive analysis which is qualitative research. Also, the researcher made a complex view of the respondents based on the real situation. The results indicate there was a considerable positive influence in society, so that it can create the enthusiasm of the community for waqf with cash.